A rural teledentistry care experience: a geriatric approach to assessing oral health status and treatment needs in older adults from a Mapuche community in Chile - Beltrán, Víctor; Muñoz-Sepúlveda, Fernanda; Acevedo, Claudia; Navarro, Pablo; Venegas, Bernardo; Salgado, Catalina; Uribe, Pablo; Engelke, Wilfried (Frontiers in Public Health, 2024)
Background: Limited attention has been given to oral health challenges faced by older Indigenous populations, especially in rural settings, where disparities exist. This study aims to assess oral health in a rural Mapuche community in southern Chile, utilizing geriatric technology support, and exploring the connection between geriatric health and oral well-being to fill a gap in this context.A cross-sectional study was conducted involving 76 independent older adults from a rural Mapuche community who required dental care. Assessments were in a remote care setting gathering extensive data including comprehensive geriatric assessments, medical and dental conditions using a geriatric teledentistry platform (TEGO®). Statistical analysis involved descriptive analysis, logistic regression, and both multiple correspondence analysis and k-means cluster analysis.The sample comprised individuals with limited formal education and a high degree of vulnerability. Geriatric assessments unveiled cognitive deterioration, frailty, depression risk, and multimorbidity. A distribution of the DMFT index, number of remaining teeth, number of occluding pairs, number of teeth with restorative needs and other relevant clinical findings was conducted based on sociodemographic, and medical-geriatric-dental characteristics, and additionally, a Multinomial Logistic Regression Analysis of Dentition Variables in Relation to Geriatric Assessments was performed. The dental burden was substantial, with an average DMFT index of 25.96 (SD 4.38), high prevalence of non-functional dentition (89.3%), periodontal disease (83%), xerostomia (63.2%) and oral mucosal lesions (31.5%). Age, lower education, depression, daily medication number and sugary consumption frequency were associated with a decreased average number of teeth (p<0.05). Multiple correspondence analysis and k-means cluster analysis identified 4 clusters, with the edentulous and functional dentition groups being the most distinct.This study uncovers a substantial dental burden and intricate medical-geriatric conditions interlinked among Indigenous older adults in a rural Chilean Mapuche community. The implementation of a geriatric technological ecosystem in the community enabled the resolution of less complex oral health issues and facilitated remote consultations with specialists, reducing the necessity for travel to health centers. This underscores the need for innovative dental public health initiatives to address health disparities and improve the overall well-being of older Indigenous adults.